PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP MANAJEMEN LABA PADA SAAT DAN SETELAH TERJADINYA FINANCIAL CRISIS DENGAN RETURN ON ASSET (ROA) SEBAGAI VARIABEL KONTROL (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2008-2011) - Vina Suhaimatul Zalfaa’ ; Abdul Ghofar,SE., M.Si., MSA., Ak.,DBA
This research aims to analyze whether there are differences in earnings management _x000D_ practices during and after financial crisis that occurred in Indonesia period 2008. In_x000D_ addition, this research also examined the influence of Good Corporate Governance_x000D_ (GCG) proxised by the Board Commissioner Independent to earnings management_x000D_ practice during and after financial crisis with Return On Assets (ROA) as a control_x000D_ variable. This research was conducted at manufacturing sector companies listed on_x000D_ Indonesia Stock Exchange (IDX) period 2008-2011 with total samples of 45_x000D_ companies in each year. The results of this research indicate that at the time of the_x000D_ occurrence of financial crisis and after the financial crisis, the average company to_x000D_ practice earnings management. However, earnings management practices in the event_x000D_ of a financial crisis is lower than after the financial crisis. In addition, Good_x000D_ Corporate Governance (GCG) which is proxied by the Board Commissioner_x000D_ Independent has a positive effect on earnings management practices at that time. _x000D_ _x000D_ Keyword: Earnings Management, Financial Crisis, Good Corporate Governance,_x000D_ Return On Asset